(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: Robson, proposed a new classification system, the Robson’s Ten Group Classification to allow critical analysis of assessing Caesarean section rate according to characteristics of pregnancy. Auditing Caesarian section rates can be done using Robson’s classification which in turns helps achieving a uniform basis for comparison across centers and across various countries. The objective was to describe caesarean rates in a tertiary care hospital of Dhaka using Robson’s Ten Groups Classification. Methods: A retrospective study was done in Dhaka Community Medical College & Hospital, Dhaka, over a period of one year January 2018 to December 2018. All cases of LUCS done during this period were classified according to Robson’s classification and analyzed. Results: A total number of 757 deliveries were conducted over this one year study period. C-Section was performed in 550 patients, giving C-section rates of 73%. Robson’s group 5 was the highest contributors to overall CS rate, contributing 28% of all C-sections, followed by group 2 and 4 combindly contributes 20% of overall CS rate (13.4% and 13.1% respectively) .The most common indications of primary C-section were failure to progress of labour (12.5%), Fetal distress (12.4%), and CPD (10.7%). Conclusions: Robson’s classification helps to identify and analyze the groups that contribute to the most to overall caesarian section rate. This may help to modify strategies and interventions to optimize caesarian section rate. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(1): 5-9